Investigating logistics service quality in omni-channel retailing. Issue 4 (2nd May 2017) - Murfield, Monique; Boone, Christopher A.; Rutner, Paige; Thomas, Rodney
Abstract : Purpose: The purpose of this paper is to investigate the impact of logistics service quality (LSQ) on consumer satisfaction and loyalty in an omni-channel retail environment. Design/methodology/approach: An empirical, survey-based approach is used to collect data from consumers about experiences with two different omni-channel retail scenarios: buy-online-pickup-in-store (BOPS), and buy-in-store-ship-direct (BSSD). Participants responded to questions regarding the LSQ, consumer satisfaction, and consumer loyalty relative to their actual experience in one of these situations. Findings: Results suggest that omni-channel consumers are truly unique, and all three dimensions of LSQ (condition, availability, and timeliness) are distinct in their impact on satisfaction and loyalty. Results suggest that in the BOPS sample, consumer satisfaction partially mediates the relationship between condition and loyalty and fully mediates the relationship between timeliness and loyalty. In the BSSD model, consumer satisfaction partially mediates the relationship between timeliness and consumer loyalty. Research limitations/implications: This research studies LSQ in two different omni-channel scenarios; additional research is needed to explore other omni-channel scenarios and extend the findings to be more generalizable. Practical implications: Managers should recognize that for omni-channel consumers, timeliness is the essential driver of satisfaction and loyalty. Retailers need to account for this reality and dedicate substantial resources to meet delivery requirements in a timely manner. Logistics service providers need to emphasize speed and reliability of their delivery processes for omni-channel consumers. Originality/value: This research is the first attempt at conceptualizing LSQ in an omni-channel supply chain, and testing the impact of LSQ on consumer satisfaction and loyalty.